Health-related quality of life is inversely correlated with C-reactive protein and age in Mycobacterium avium complex lung disease: a cross-sectional analysis of 235 patients. Issue 1 (December 2015) - Asakura, Takanori; Funatsu, Yohei; Ishii, Makoto; Namkoong, Ho; Yagi, Kazuma; Suzuki, Shoji; Asami, Takahiro; Kamo, Tetsuro; Fujiwara, Hiroshi; Uwamino, Yoshifumi; Nishimura, Tomoyasu; Tasaka, Sadatomo; et al.
Abstract Background Mycobacterium avium complex (MAC) lung diseases generally cause chronic disease in immunocompetent hosts. Although a few studies have examined health-related quality of life (HRQL) in patients with MAC lung disease, there have been no large studies. This study aimed to evaluate HRQL and its correlation with clinical outcomes in MAC lung disease. Methods A cross-sectional study was conducted at Keio University Hospital to investigate the factors associated with HRQL in pulmonary nontuberculous mycobacterial diseases. MAC lung diseases were diagnosed according to the 2007 ATS/IDSA guidelines for nontuberculous mycobacterial diseases. The 36-item short form health survey (SF-36) was administered to assess clinical outcomes. Clinical variables included treatment status, latest haematological data, and bacterial smear and culture results. Results The SF-36 scores for the 235 patients (median age, 69 years; 45 men and 190 women) with MAC lung disease, except for the bodily pain and mental health subscale scores, were significantly lower than the Japanese population norms. In the multivariable analyses, current treatment for MAC and a positive sputum smear or culture within the past year were significantly associated with lower SF-36 scores. C-reactive protein (CRP) and age showed stronger inverse correlations with SF-36 scores. Conclusions HRQL, especially the physical component, was impaired in patients with MAC lung diseases; this appears to be related with current treatment status, positive sputum smear or culture within the previous year, and particularly CRP and age. Further studies including qualitative assessments are needed to investigate the efficacy of CRP as a marker for progression or treatment response in MAC lung disease. Trial registration Clinical trial registered with UMIN (UMIN000007964 ).